A Comparative Study on the Approach to Legal Capacity in the Convention on the Rights of Persons with Disabilities and Iranian Law - Mohammad Keyvan; Sepanta Mojtahedzadeh; Ehsan Shahsavari (پژوهشنامه حقوق تطبیقی)
The concept of legal capacity is fundamental in the realm of human rights, as its deprivation can lead to widespread violations of rights. Individuals with disabilities often face denial of this right for various reasons. This article, written in a descriptive-analytical and comparative manner, examines the concept of legal capacity, its types, and the significance of individuals benefiting from it. We aim to address the critical question: Has the Convention on the Rights of Persons with Disabilities, particularly Article 12, brought about a fundamental change in the situation of people with disabilities? The answer is that the convention, especially Article 12, effectively eliminates any form of disqualification for individuals with disabilities. Furthermore, the provisions within this treaty provide the necessary framework to transform their legal status. The convention and its evolving interpretation advocate for the establishment of a new legal structure based on protection rather than guardianship. The second question of this research is: What is the capacity system in the laws of the Islamic Republic of Iran concerning the status of cognitively disabled individuals, and is it compatible with Iran's international obligations and the support system outlined by the convention? The answer is that the capacity system in Iran's laws regarding cognitively disabled individuals still retains a traditional framework, in which capacity is denied to the individual and assigned to their guardian.